Pengaruh Harga dan Online Customer Review Terhadap Minat Beli Produk Skincare Scarlett Pada Pengguna Shopee - Yuliana Arsita; Hartanti Nugrahaningsih; Ecin Kuraesin (Institute of Advanced Knowledge and Science, 2023)
The purpose of this study was to determine the effect of price and online customer reviews on buying interest in Scarlett skincare products for Shopee users. This type of research is quantitative research. The sampling technique was carried out using the Slovin formula. The sample used was 90 respondents. The testing tool used is SPSS v25 software. The analysis technique used is multiple linear regression analysis, multiple correlation analysis. The results of this study indicate partially that the price and online customer review variables have a significant effect on buying interest. Simultaneously, the price and online customer review variables have a significant effect on purchase intention, In addition, the coefficient of determination shows that the effect of X1 and X2 on Y is 0.437 = 43.7% and the remaining 56.3% is influenced by variables outside the model studied.